The probatory rules and the need for their application at the judgment stage. Doing it is good judicial practice - Gutiérrez Gutiérrez, Carlos Germán (2016)
Although our Peruvian Procedural Code does not regulate the evidentiary conventions at the trial stage, the author states that circumstances exist and justify its application at that stage, as they are: the lack of knowledge of theory of the case, the consent of the accused, not violate the probative discussion, the change of «notorious fact» for «undisputed fact», as well as simplification and the speed of trial. It explains three specific cases where evidentiary conventions were formulated at the stage of trial, concluding that although there is no express provision which allows implementation, neither exists compatibility in order to accept those evidentiary conventions which have not been previously promoted by the legal parties, therefore it proposes a legislative amendment.